The rhythms of change in the teaching-learning of periodization. A proposal from global history (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2020)
This study is about the representations of the rhythms of change in the process of teaching/learning of high school students. Both historical time and the rhythms of change are paramount to understanding temporality. Current contexts are marked by their accelerated changes and their constant contradictions. To be able to read the world requires not only aspects of connection and integration, but also evidence of conflicts, the contradictions and differences that coexist in human groups. The methodology is qualitative in nature with a mixed design, the instruments used correspond to: questionnaires, personal narratives and curricular documents. Among the results we can mention the linear and irreversible representation of time continues to have as a consequence of curriculum that emphasizes the chronological aspects of historical time. However, 95.6% of the student recognizes the change and easily associates it with those transformations of rapid duration on a personal level. In the field of global history, the curriculum considers the different scales to deal with the contents (local, regional and global) however the temporal interrelations are limited to a single understanding: the European one.
Keywords: time; change; periodization; global history; didactics of social sciences